Two-photon polymerized "nichoid" substrates maintain function of pluripotent stem cells when expanded under feeder-free conditions. Issue 1 (December 2016) - Nava, Michele; Piuma, Alessio; Figliuzzi, Marina; Cattaneo, Irene; Bonandrini, Barbara; Zandrini, Tommaso; Cerullo, Giulio; Osellame, Roberto; Remuzzi, Andrea; Raimondi, Manuela
Abstract Background The use of pluripotent cells in stem cell therapy has major limitations, mainly related to the high costs and risks of exogenous conditioning and the use of feeder layers during cell expansion passages. Methods We developed an innovative three-dimensional culture substrate made of "nichoid" microstructures, nanoengineered via two-photon laser polymerization. The nichoids limit the dimension of the adhering embryoid bodies during expansion, by counteracting cell migration between adjacent units of the substrate by its microarchitecture. We expanded mouse embryonic stem cells on the nichoid for 2 weeks. We compared the expression of pluripotency and differentiation markers induced in cells with that induced by flat substrates and by a culture layer made of kidney-derived extracellular matrix. Results The nichoid was found to be the only substrate, among those tested, that maintained the expression of the OCT4 pluripotency marker switched on and, simultaneously, the expression of the differentiation markers GATA4 and α-SMA switched off. The nichoid promotes pluripotency maintenance of embryonic stem cells during expansion, in the absence of a feeder layer and exogenous conditioning factors, such as the leukocyte inhibitory factor. Conclusions We hypothesized that the nichoid microstructures induce a genetic reprogramming of cells by controlling their cytoskeletal tension. Further studies are necessary to understand the exact mechanism by which the physical constraint provided by the nichoid architecture is responsible for cell reprogramming. The nichoid may help elucidate mechanisms of pluripotency maintenance, while potentially cutting the costs and risks of both feed-conditioning and exogenous conditioning for industrial-scale expansion of stem cells.